Effects of air pollution caused by sugarcane burning in Western São Paulo on the cardiovascular system - Paula Roberta da Silva Pestana; Alfésio Luís Ferreira Braga; Ercy Mara Cipulo Ramos; Ariadna Ferraz de Oliveira; Christian Robert Osadnik; Aline Duarte Ferreira; Dionei Ramos
ABSTRACT OBJECTIVE To evaluate the effects of acute exposure to air pollutants (NO2 and PM10) on hospitalization of adults and older people with cardiovascular diseases in Western São Paulo. METHODS Daily cardiovascular-related hospitalization data (CID10 - I00 to I99) were acquired by the Department of Informatics of the Brazilian Unified Health System (DATASUS) from January 2009 to December 2012. Daily levels of NO2 and PM10 and weather data were obtained from Companhia Ambiental do Estado de São Paulo (CETESB - São Paulo State Environmental Agency). To estimate the effects of air pollutants exposure on hospital admissions, generalized linear Poisson regression models were used. RESULTS During the study period, 6,363 hospitalizations were analysed. On the day of NO2 exposure, an increase of 1.12% (95%CI 0.05-2.20) was observed in the interquartile range along with an increase in hospital admissions. For PM10, a pattern of similar effect was observed; however, results were not statistically significant. CONCLUSIONS Even though with values within established limits, NO2 is an important short-term risk factor for cardiovascular morbidity.